Answer :

xb – ay = ab × 0

xb – ay = 0 ……(1)

ax + by = a^{2} + b^{2}……(2)

Eliminate (1) and (2)

(xb – ay = 0) × a

(ax + by = a^{2} + b^{2}) × b

– a^{2}y – b^{2}y = – a^{2}b + b^{3}

– y (a^{2} + b^{2}) = – b (a^{2} + b^{2})

y = b

Put y = b in (1)

xb – ab = 0

xb = ab

x = a

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Goprep Genius Quiz on Linear Equations34 mins

Interactive session on Linear Equations in Two VariablesFREE Class

NCERT | Linear Equations41 mins

Quiz | Testing Your Skills on Linear Equation in Two Variables36 mins

Quiz | Important Questions on Linear Equations In Two Variables49 mins

Champ Quiz | Do you Know about Linear Equations ?35 mins

Master Linear Equations40 mins

Quiz | Imp. Qs. on Linear Equations44 mins

Quiz | Solve Problems on Linear Equations37 mins

Champ Quiz | Linear Equation45 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation

RELATED QUESTIONS :

Express y in terms of x, given that Check whether ( – 5, 2) is a solution of the given equation.

RS Aggarwal & V Aggarwal - MathematicsWrite two solutions for each of the following equations:

(i) 3*x*+4*y* =7

(ii) *x*=6*y*

(iii) *x*+π*y* =4

(iv) *x*-*y* =4

How many linear equations are satisfied by *x*=2 and *y*=-3?

If (2*k*-1,*k*) is a solution of the equation 10*x*-9*y*=12, then *k*=

If (*a*,4) lies on the graph of 3*x*+*y*=10, then the value of *a* is